Existence of Tripled Fixed Points for a Class of Condensing Operators in Banach Spaces - Vatan Karakaya; Nour El Houda Bouzara; Kadri Doğan; Yunus Atalan (The Scientific World Journal)
We give some results concerning the existence of tripled fixed points for a class of condensing operators in Banach spaces. Further, as an application, we study the existence of solutions for a general system of nonlinear integral equations.